An evaluation of Brazil's surveillance and prophylaxis of canine rabies between 2008 and 2017. - Julio A Benavides; Jane Megid; Aline Campos; Silene Rocha; Marco A N Vigilato; Katie Hampson (Public Library of Science (PLoS), 2019)
An effective surveillance system is critical for the elimination of canine rabies in Latin America. Brazil has made substantial progress towards canine rabies elimination, but outbreaks still occurred in the last decade in two states. Brazil uses a health information system (SINAN) to record patients seeking post-exposure prophylaxis (PEP) following contact with an animal suspected of having rabies. This study evaluated: (i) whether SINAN can be reliably used for rabies surveillance; (ii) if patients in Brazil are receiving appropriate PEP and (iii) the benefits of implementing the latest World Health Organization (WHO) recommendations on PEP. Analysing SINAN records from 2008 to 2017 reveals an average of 506,148 bite-injury patients/year [range: 437k-545k] in the country, equivalent to an incidence of 255 bite-injuries/100,000 people/year [range: 231-280]. The number of reports of bites from suspect rabid dogs generally increased over time. In most states, records from SINAN indicating a suspect rabid dog do not correlate with confirmed dog rabies cases reported to the Regional Information System for Epidemiological Surveillance of Rabies (SIRVERA) maintained by the Pan American Health Organization (PAHO). Analyses showed that in 2017, only 45% of patients received appropriate PEP as indicated by the Brazilian Ministry of Health guidance. Implementation of the latest WHO guidance using an abridged intradermal post-exposure vaccination regimen including one precautionary dose for dog bites prior to observation would reduce the volume of vaccine required by up to 64%, with potential for annual savings of over USD 6 million from reduced vaccine use. Our results highlight the need to improve the implementation of SINAN, including training of health workers responsible for delivering PEP using an Integrated Bite Case Management approach so that SINAN can serve as a reliable surveillance tool for canine rabies elimination.